Comparison of Biofeedback Therapy in Children With Treatment-refractory Dysfunctional Voiding and Overactive Bladder - (:unkn) unknown (ELSEVIER SCIENCE INC, 2015)
OBJECTIVE To evaluate and compare the effectiveness of biofeedback therapy (BF) in children with treatment refractory overactive bladder (OAB) and dysfunctional voiding (DV). METHODS This study was performed between April 2012 and March 2014. Patients with treatment refractory OAB and DV were included. All patients had 3 months of BF. Patients' urologic system symptoms and uroflow parameters before BF and 3 months after BF and response rates were compared. RESULTS Forty-five patients completed the study. Significant improvement was seen in urinary tract infections, urge incontinence, fractionated voiding, constipation, voided volume, maximum flow rate (Qmax), average flow rate (Qave), and postvoiding residue for patients with DV and in urinary tract infection, frequency, urge incontinence, Qmax, Qave, voiding time, and postvoiding residue for patients with OAB. Overall, better results were observed in patients with DV. CONCLUSION BF is an effective treatment modality in children with treatment refractory OAB and DV; however, patients with DV show better improvement. (C) 2015 Elsevier Inc.
Keywords: PELVIC-FLOOR; NOCTURNAL ENURESIS; STIMULATION